2016
DOI: 10.3390/nu8050303
|View full text |Cite
|
Sign up to set email alerts
|

Asiatic Acid Prevents the Deleterious Effects of Valproic Acid on Cognition and Hippocampal Cell Proliferation and Survival

Abstract: Valproic acid (VPA) is commonly prescribed as an anticonvulsant and mood stabilizer used in the treatment of epilepsy and bipolar disorder. A recent study has demonstrated that VPA reduces histone deacetylase (HDAC) activity, an action which is believed to contribute to the effects of VPA on neural stem cell proliferation and differentiation which may explain the cognitive impairments produced in rodents and patients. Asiatic acid is a triterpenoid derived from the medicinal plant Centella asiatica. Our previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 53 publications
(78 reference statements)
1
42
0
Order By: Relevance
“…The OLM is a hippocampal‐dependent test of location memory (Assini, Duzzioni, & Takahashi, ; Cipolotti, ) which is known to be impaired with aging in both humans and rodents (Arias‐Cavieres, Adasme, Sánchez, Muñoz, & Hidalgo, ; Sapkota, van der Linde, Lamichhane, Upadhyaya, & Pardhan, ; Wimmer, Hernandez, Blackwell, & Abel, ). The improvement in the OLM seen in this study is consistent with previous studies showing that asiatic acid, a major triterpene component of Centella asiatica (Siddiqui, Aslam, Ali, Khan, & Begum, ), improves performance in the same task in healthy as well as cognitively impaired rodents (Chaisawang et al., ; Sirichoat et al., ; Umka Welbat et al., ). It is also in line with reports that OLM performance by aged mice is improved by treatment with polyphenols (Carey, Gomes, & Shukitt‐Hale, ; Matsui et al., ), a class of compounds which both Centella asiatica in general (Siddiqui et al., ; Subban, Veerakumar, Manimaran, Hashim, & Balachandran, ) and CAW specifically are rich in (Gray, Zweig, Matthews, et al., ; Gray, Zweig, Murchison, et al., ; Soumyanath et al., ).…”
Section: Discussionsupporting
confidence: 91%
“…The OLM is a hippocampal‐dependent test of location memory (Assini, Duzzioni, & Takahashi, ; Cipolotti, ) which is known to be impaired with aging in both humans and rodents (Arias‐Cavieres, Adasme, Sánchez, Muñoz, & Hidalgo, ; Sapkota, van der Linde, Lamichhane, Upadhyaya, & Pardhan, ; Wimmer, Hernandez, Blackwell, & Abel, ). The improvement in the OLM seen in this study is consistent with previous studies showing that asiatic acid, a major triterpene component of Centella asiatica (Siddiqui, Aslam, Ali, Khan, & Begum, ), improves performance in the same task in healthy as well as cognitively impaired rodents (Chaisawang et al., ; Sirichoat et al., ; Umka Welbat et al., ). It is also in line with reports that OLM performance by aged mice is improved by treatment with polyphenols (Carey, Gomes, & Shukitt‐Hale, ; Matsui et al., ), a class of compounds which both Centella asiatica in general (Siddiqui et al., ; Subban, Veerakumar, Manimaran, Hashim, & Balachandran, ) and CAW specifically are rich in (Gray, Zweig, Matthews, et al., ; Gray, Zweig, Murchison, et al., ; Soumyanath et al., ).…”
Section: Discussionsupporting
confidence: 91%
“…Several recent studies have demonstrated pharmacological effects of C. asiatica triterpenoids, particularly AA and AS, in various rodent models including those related to memory and learning assessment, where bioactive compound needs to reach brain tissue [18,39,40]. As a preliminary estimation of potency to relate our results to in vivo neurological responses, the apparently bioactive doses of AA or AS from memory and learning behavioral studies using similar animal species, oral administration of test compound, and purified test compounds from commercial source were compared.…”
Section: Discussionmentioning
confidence: 99%
“…As a preliminary estimation of potency to relate our results to in vivo neurological responses, the apparently bioactive doses of AA or AS from memory and learning behavioral studies using similar animal species, oral administration of test compound, and purified test compounds from commercial source were compared. The effective doses of AA and AS were shown to be 30 mg/kg/d and between 5 and 45 mg/kg/d, respectively, indicating that AS could be slightly more potent (about two-fold) when the molecular weights of both compounds are accounted [39,40]. Based on bioavailability data from two independent reports, the bioavailability of AA (16.25 %, 20 mg/kg administered orally) appeared approximately ten times higher than that of AS (1.86 %, 38 mg/kg administered orally), implying a much higher potency of AS than AA if bioactivities are only originated from intact molecules [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…impairment of cell proliferation, spatial working memory caused by treatment with valproic acid [75]. Water extract helped to improve cognitive function by activation of antioxidant response gene and mitochondrial biogenesis [76], normalized calcium homeostasis [77].…”
Section: Prakash Et Almentioning
confidence: 99%